DISPENSASI KAWIN YANG DIBERIKAN KEPADA ANAK DI BAWAH UMUR DI PENGADILAN AGAMA KELAS 1A PADANG - Putri Hanifah dan Mardius (Normative Jurnal Ilmiah Hukum, 2021)
Law No. 16 of 2019 concerning amendments to law No.1 of 1974 concerning marriage. Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal (household) based on the One Godhead. Marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. The prospective bride and groom who have not met the minimum age specified by law, the prospective bride and groom must ask for dispensation of marriage to the religious court. The problem in this research is how is the implementation of the dispensation of marriage given to minors in the Padang religious court and whether the judges consider the dispensation of marriage given to minors in the Padang religious court. This research uses a sociological juridical approach, while the nature of the research is descriptive. For minors to marry, the applicant first submits a letter of rejection from the Office of Religious Affairs (KUA), then this is used as the basis for submitting a dispensation request to the Religious Court. The first stage that takes place is that the parents of the woman or both parents of the male party make a request that is submitted to the head of the Religious Court. The judge's consideration of the dispensation of marriage by minors in the Religious Court The judge gives dispensation to the applicant because the child someone is responsible because the applicant's mother has died and so that unwanted things do not happen because they have been in a relationship for a long time.